PENANGANAN PERMASALAHAN PERILAKU KORUPTIF PADA ANAK MUDA DENGAN MENERAPKAN SISTEM PENDIDIKAN ANTI KORUPSI - Fernando Tobing (Jurnal Ilmu Hukum Sui Generis, 2022)
Corruption can be a threat that can divide the unity of Indonesia. The education system that is relied on, namely in the form of anti-corruption education, is hoped to be a way out that is sufficient to help the community in developing a spirit of anti-corruption behavior, because one small form of corruption comes from the family. In the family, moreover a harmonious family itself does not rule out the possibility that corruption can be avoided, let's just say that the child's behavior is a reflection of his parents, whether the parents do actions that we consider normal every day, but according to ethics, morals and law , this action is a reflection that is wrong when shown to children. Corrupt behavior can become a entrenched problem if it is not immediately eradicated, through several methods such as showing courage, fairness and wisdom.